“Autogangs”. Car Smuggle to Communist Poland in the 1980s - Nawrocki, Karol (Studia Historiae Oeconomicae, 2016)
The article refers to the economic consequences of the post-war division of Europe into the capitalist West and communist East. One of the consequences of this division was the creation of peculiar crime phenomenon on the eastern side of the “iron curtain”, which consist on exploit the prices and goods availability differences between wealthy West and backward East of Europe. This being the case of illegal movement of goods, begun from the 1940s, between those two worlds. In article you can find the outline of characteristic for the whole Polish “People’s” Republic period smuggling conducts. The key subject of following text is first of all the problem of car smuggling in the 1980s, which wasn’t researched by polish historians before. In this interesting for us times in Western Europe (West Germany, Austria, France) and in Scandinavia at least few groups of organized crime were active in a areas of car stealing and smuggling a luxury goods into Poland. The essence of following article are the presentation of these groups, their bosses, criminal practices and techniques and indication of the cooperation between polish car smugglers and western countries citizens. Sources for this text are based first of all on operational and investigation records of former Security Service collected in archives of the Institute of National Remembrance.